New sinoalids (Insecta: Hemiptera: Cercopoidea) from Middle to Upper Jurassic strata at Daohugou, Inner Mongolia, China. Issue 2 (3rd April 2019) - Fu, Yanzhe; Huang, Diying
Abstract : Fu, Y., & Huang, D., December 2018. New sinoalids (Insecta: Hemiptera: Cercopoidea) from Middle to Upper Jurassic strata at Daohugou, Inner Mongolia, China. Alcheringa 43, 246–256. ISSN 0311-5518. A new fossil genus with three species of Sinoalidae, Parasinoala daohugouensis gen. et sp. nov., Parasinoala minuta gen. et sp. nov., Parasinoala magnus gen. et sp. nov., from the Middle to Upper Jurassic Haifanggou Formation at Daohugou, Inner Mongolia, northeastern China, is described and illustrated. The new genus differs from other sinoalids by the tegmen with RA having 2–3 branches, MP with 3–4 branches and MP of hind wings with two branches, which indicates the terminal branches of RA and MP are highly variable within Sinoalidae. The new discovery greatly increases the palaeodiversity of sinoalids in the early assemblage of the Yanliao biota from the Daohugou beds. Yanzhe Fu [ yzfu@nigpas.ac.cn ] State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology, Chinese Academy of Sciences, Nanjing 210008, PR China ; University of Science and Technology of China, Hefei 230026, PR China ; Diying Huang * [dyhuang@nigpas.ac.cn ] State Key Laboratory of Palaeobiology and Stratigraphy, Center for Excellence in Life and Paleoenvironment, Nanjing Institute of Geology and Palaeontology, Chinese Academy of Sciences, Nanjing 210008, PR China.